2021
DOI: 10.1016/j.icarus.2020.114098
|View full text |Cite
|
Sign up to set email alerts
|

A statistical review of light curves and the prevalence of contact binaries in the Kuiper Belt

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 58 publications
(104 reference statements)
0
34
1
Order By: Relevance
“…We compared our cumulative amplitude distribution with those discussed in Showalter et al (2021). To obtain the cumulative amplitude distribution curve of our K2 sample, we considered both the targets with detected periods and welldetermined amplitudes and those that only have amplitude upper limits (see Figure 4).…”
Section: Amplitude Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared our cumulative amplitude distribution with those discussed in Showalter et al (2021). To obtain the cumulative amplitude distribution curve of our K2 sample, we considered both the targets with detected periods and welldetermined amplitudes and those that only have amplitude upper limits (see Figure 4).…”
Section: Amplitude Distributionmentioning
confidence: 99%
“…In the same figure, we also plot the "Combined," "Centaur," and "OSSOS" curves from Showalter et al (2021), which mostly use ground-based data. We also plot the original cumulative amplitude curve derived by the Thousand Asteroid Light Curve Survey (Masiero et al 2009) to cover the main belt asteroids.…”
Section: Amplitude Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the New Horizons spacecraft revealed that Arrokoth is a contact binary, which likely resulted from a low-speed merger of two flattened, spheroidal components (Stern et al 2019). Additionally, light curve observations of TNOs indicate that the contact binary fraction can be 30% or higher (Sheppard and Jewitt 2004;Thirouin and Sheppard 2018, 2019Noll et al 2020;Showalter et al 2021).…”
Section: Morphological Evolution and Tno Binaries In Contextmentioning
confidence: 99%
“…This introduces a fairly wide dispersion in the phase curve, as shown in Figure 2. For this work, to achieve some consistency given this issue, we have chosen the mean value of the magnitude in cases where there was more than one observation per day (Showalter et al 2020).…”
Section: Gaia Datamentioning
confidence: 99%